REPRESENTASI KESAKTIAN DATU DALAM LEGENDA “ASAL MULA PULAU HALIMUN DAN GUNUNG JAMBANGAN” MELALUI ANALISIS STRUKTURAL LEVI-STRAUSS - Musdalipah Musdalipah (Kelasa, 2017)
AbstractDatu in Banjarese society is similar to wali in Javanese society. Datu is represented as an old manwho has supernatural and magical powers. The supernatural powers are achieved through hisobedience and closeness to the Creator of the Universe. The problem is how the datu’ssupernatural powers in the legend “Asal Mula Pulau Halimun dan Gunung Jambangan (The Originof Halimun Island and Jambangan Mountain)” represents the supernatural powers of datu inBanjarese sociey? The aim of this research is to figure out all supernatural powers of datu in thelegend “Asal Mula Pulau Halimun dan Gunung Jambangan (The Origin of Halimun Island andJambangan Mountain)” as the representation of datu supernatural powers in Banjarese society.The research uses qualitative and descriptive method using Levi-Strauss’ structural analysistechnique. The result of this research is that there are some supernatural powers of Datu Mabrurwhich are the representation of datu supernatural powers in Banjarese society. The supernaturalpowers are (1) the ability to fight attack from the todak fish and its supernatural king, (2) theability to perform long distance communication with other datus, (3) the ability to carry dozens ofulin trees for hundreds kilometers on his shoulder, and (4) the ability to carry a big mountain on hisshoulder. AbstrakDatu pada masyarakat Banjar seperti wali pada masyarakat Jawa. Sosok datu dimaknai sebagaiseorang lelaki tua yang memiliki kesaktian dan karomah. Kesaktian ini diperoleh dari ketaatan dankedekatannya terhadap Sang Pencipta alam semesta. Masalahnya, bagaimana kesaktian tokohdatu yang ada pada legenda “Asal Mula Pulau Halimun dan Gunung Jambangan” sebagairepresentasi kesaktian para datu pada masyarakat Banjar? Tujuan penelitian ini adalahmenemukan kesaktian tokoh datu yang ada pada legenda “Asal Mula Pulau Halimun dan GunungJambangan” sebagai representasi kesaktian para datu pada masyarakat Banjar. Metode yangdigunakan adalah metode kualitatif dan deskriptif, dengan teknik analisis struktural Levi-Strauss.Hasil penelitian ini adalah menemukan beberapa kesaktian Datu Mabrur sebagai representasikesaktian para datu pada masyarakat Banjar. Yakni (1) mampu melawan serangan kelompok ikantodak beserta rajanya yang sakti, (2) mampu berkomunikasi jarak jauh dengan datu yang lain, (3)mampu menggotong berpuluh-puluh pohon ulin dengan jarak ratusan kilometer, dan (4) mampumenggotong gunung besar.